Joe Biden's policies on abortion and immigration: the challenges of the second Catholic president - Formicola, Jo Renée (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The first part of Joe Biden’s Policies on Abortion and Immigration examines the policy quandaries that arise from the fact that President Biden considers himself a liberal, a Catholic, and a Democrat. That self-identification has challenged aspects of his leadership and governance that have resulted in growing national controversies surrounding his abortion and immigration policies. Thus, this book articulates Catholic moral and social teachings on these issues, the president’s perceived religious beliefs that often clash with his personal views and values, as well as his opposing political responses to them. It also explains his partisan actions to abortion and immigration that include numerous executive orders, appointments of individuals who are unable to help him develop solutions to such critical matters, and his criticisms of the Congress, the Supreme Court, and previous administration officials.The second part of this book, then, gives examples of how policy difficulties have been overcome by various government leaders who have also dealt with critical decision-making and agenda options. It provides historical models, management methods, communication strategies, and religious principles that can be utilized to create pragmatic solutions to the problems of immigration and abortion. They can also be implemented by the president while also helping him to instill a sense of unity and justice on these policy issues in the United States.